The Effect of Liquidity Ratio and Activity Ratio on the Financial Performance of PT. Smart Millenium Efessiens for the 2017-2024 Period - Ercika Kaban (Managing: Jurnal Bisnis dan Manajemen, 2025)
This study aims to analyze the effect of the liquidity ratio (Current Ratio) and activity ratio (Total Asset Turnover) on the financial performance (Return on Investment) of PT Smart Milenium Effesiensi during the 2017–2024 period. The research method used is a quantitative approach with documentation and literature study techniques. Data were analyzed using multiple linear regression with IBM SPSS 25 software. The results showed that partially, the Current Ratio had a positive effect of 0.013 on ROI, while Total Asset Turnover also had a positive effect of 0.004 on ROI. Simultaneously, both variables significantly affected financial performance. These findings indicate that effective asset management and good liquidity contribute to the company’s profitability.